JULEHA (HALAL SLAUGHTERER): BETWEEN PROFESSION AND TRADITION - Atieqoh, Siti; Fauziah, Fauziah; Zuhrah, Fatimah; Warnis, Warnis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Halal slaughtermen as a national and global strategic profession are contrary to the needs of halal slaughterhouse workers have not been met. The sociological understanding of halal slaughters workers has not been revealed. This study was designed to reveal the sociological condition of halal slaughters and the challenges they face as a profession or are still traditional. The perceptions and awareness of actors and service users regarding the role of halal butchers in halal ecosystem will be explored in this research as well as effective social policy approaches that can be implemented. The position and sociological role of the halal slaughter worker is studied phenomenologically. In-depth interviews, focus group discussions and observations were carried out for data collection. Informants came from the province of Yogyakarta with a purposive sampling technique, who have slaughterhouses. Qualitative analysis through data reduction, data presentation and drawing conclusions was carried out to describe how halal slaughterers are perceived. The description is deepened in terms of the challenges faced by halal slaughters as a profession. For this reason, researchers use agency theory and Giddens' structuration as a theoretical framework in explaining social action with the ultimate goal of finding appropriate social policies needed to be implemented.